Production of low calorie beer a plant design - Camance, Aldwin; Cortes, Joselito Y.; Galicia, Carmilla Marie Guadalupe T.; Mangalindan, Shallini (College of Engineering, 1998)
Main product: low calorie beer -- Main raw material: malt, rice, hops and enzyme -- Plant location: Barrio Bucal, Calamba, Laguna -- Plant area: One hectare -- Annual volume of production: 3020 m3 (9,437,500 bottles) -- Annual sales: Php 94,375,000.00,(80% cap) -- Annual income: Php 22,121,851.55 -- Total capital investment: Php 70,000,000.00 -- Product unit cost: Php 5.43 -- Suggested product selling price: Php 12.50 -- Average rate of ROI: 27.8% -- Payback period: 5.52 months -- Net turnover: 0.28 -- Break-even capacity: 3,303,125 bottles